Tidal Ellipses Analysis Based on Flow Model Hydrodynamic Data Acquisition in Mandeh Bay, West Sumatera - Ulung Jantama Wisha; Ruzana Dhiauddin; Wisnu Arya Gemilang (Journal of Geoscience, Engineering, Environment, and Technology, 2019)
Mandeh Bay is threatened by sedimentation issue caused by the rapid development of marine tourism area which strongly impacts to the environmental degradation. Due to the semi-enclosed area of Mandeh Bay, the tidal current has a significant role in triggering vertical and horizontal transports within the bay. This study aimed to determine the characteristic of tidal current during the southwest monsoon. We developed a hydrodynamic model based on Navier-Stokes equations using a flexible mesh and tidal forecast in which the validation is performed by ADCP data. The simulation results will be used as the basic data to develop a model which depicts the elliptical pattern of tidal current constituents. Offshore rotary tidal currents which are originally semidiurnal reiterate the elliptical pattern every 6 hours and 12 minutes. The strongest semidiurnal current speeds are observed in the bay mouth ranged from 0.1-0.5 m.s-1. The tidal constituent ellipses are oriented more meridionally and in several areas oriented zonally. The current speed of is the highest at all which the speed is averagely one third of magnitude. While, the two main diurnal tidal constituents ( and ) have the maximum speeds approximately one fifth of magnitude. Thus, the domination of semidiurnal constituents may trigger sediment distribution and accumulation within the bay because of its twice tidal oscillations entering the bay.